The three-dimensional life cycles of potential vorticity cutoffs: a global and selected regional climatologies in ERA-Interim (1979–2018) - Portmann, Raphael; Sprenger, Michael; Wernli, Heini (Weather and Climate Dynamics, 2021)
The aim of this study is to explore the nature of potential vorticity (PV) cutoff life cycles. While climatological frequencies of such near-tropopause cyclonic vortices are well known, their life cycle and in particular their three-dimensional evolution is poorly understood. To address this gap, a novel method is introduced that uses isentropic air parcel trajectories to track PV cutoffs as three-dimensional objects. With this method, we can distinguish the two fundamentally different PV cutoff lysis scenarios on isentropic surfaces: complete diabatic decay vs. reabsorption by the stratospheric reservoir. This method is applied to the ERA-Interim dataset (1979–2018), and the first global climatology of PV cutoffs is presented that is independent of the selection of a vertical level and identifies and tracks PV cutoffs as three-dimensional features. More than 150 000 PV cutoff life cycles are identified and analyzed. The climatology confirms known frequency maxima of PV cutoffs and identifies additional bands in subtropical areas in the summer hemispheres and a circumpolar band around Antarctica. The first climatological analysis of diabatic decay and reabsorption shows that both scenarios occur equally frequently – in contrast to the prevailing opinion that diabatic decay dominates. Then, PV cutoffs are classified according to their position relative to jet streams (equatorward (Type I), between two jets (Type II), and poleward (Type III)). A composite analysis shows distinct dynamical scenarios for the genesis of the three types. Type I forms due to anticyclonic Rossby wave breaking above subtropical surface anticyclones and hardly results in precipitation. Type II results from anticyclonic Rossby wave breaking in mid-latitudes in regions with split-jet conditions and is frequently accompanied by surface cyclogenesis and substantial precipitation. Type III cutoffs preferentially form due to cyclonic Rossby wave breaking within extratropical cyclones in the storm track regions. We show that important track ...